Review of policies adopted in 34 Countries to improve diet and physical activity (Italian Journal of Public Health, 2011)
Background: Today, obesity can be considered in most OECD and EU countries as an unprecedented public health challenge which has been underestimated, poorly assessed and not fully accepted as a strategic governmental problem with substantial economic implications.The aim of this paper is to provide a review of the major policy statements on diet and physical activity adopted in 34 OECD and other EU countries until 2008, and to point out similarities and differences between country approaches and factors that may explain them.Methods: Information about policies and interventions was mainly retrieved from official sources such as the WHO Regional Office for Europe nutrition policy database, and websites of Health Ministries and national public health institutions.Results: The review pointed out that almost all WHO and OECD Member States have government-approved policies on nutrition and food safety. Although countries have large data and documents on overweight and obesity, they do not seem to rely on them to define clear strategies and plans for action which, as a result, are often vague and unspecific.Conclusions: In order to reverse the obesity trend down to decent levels and to reach the lower socio-economic groups, concerted, multisectorial, long-term actions are needed in combination with a much larger political determination.
Keywords: obesity; policies; OECD EU countries; diet; physical activity